Analysis of Mathematical Communication Ability Based on Learning Activity and Gender of MTs Students - Siti Utufina Widuri; Windia Hadi (Universitas Negeri Makassar, 2022)
This study aims to analyze mathematical communication skills based on learning activity and gender of MTs students. The research method used is a descriptive qualitative method. The total population in this study were 27 students of class VIII, consisting of 9 male students and 18 female students. This subject selection process uses the Wright Maps table in the Winsteps application. The selected subjects are 5 people consisting of 1 student who has high learning activity, 2 students who have medium learning activity, and 2 students who have low learning activity. Each level of learning activity consists of male and female gender. Selected subjects are given a description test and interview questions to analyze their mathematical communication skills. The results showed that male students have better mathematical communication skills than female students. Overall, students with male gender are able to fulfill two out of three indicators of mathematical communication skills. While students with female gender are only able to fulfill one of the three indicators of mathematical communication skills.